Clinical findings and management of 153 horses with large colon sand accumulations. Issue 6 (19th June 2017) - Kilcoyne, Isabelle; Dechant, Julie E.; Spier, Sharon J.; Spriet, Mathieu; Nieto, Jorge E.
Abstract: Objective: To determine the influence of radiographic quantification of sand accumulation on the medical versus surgical management of large colon sand accumulations. To compare short‐ and long‐term outcomes and complications associated with medical and surgical management of these horses. Study design: Retrospective. Sample population: A total of 153 horses. Methods: Medical records and abdominal radiographs of horses presented for colic between 2004 and 2014 were reviewed. Severity of sand accumulation was quantified by tracing and measuring a region of interest with a commercial software program. Breed, weight, amount of sand, presence of diarrhea at presentation, treatment, and the development of complications were recorded. Results: Records from 153 horses were reviewed. The mean cross‐sectional area of sand accumulation was 692.9 cm 2 (median = 658.7 cm 2, 84.6‐1780.7 cm 2 ). Increased accumulation of gas on radiographs and abnormal transrectal examination findings were associated with an increased likelihood of surgery. The most common complication was the development of diarrhea (20.3%) with only 4 (2.6%) horses positive for Salmonella spp. Horses had a favorable prognosis, with 94.8% of horses treated medically and 94.7% of those treated surgically surviving to discharge. Conclusion: Increased accumulation of gas on radiographs and transrectal palpation of impaction or intestinal gas distension increase the likelihood of surgery. Both medical and surgical treatments carry a good prognosis. Clinical relevance: The sheer quantity of sand is not a factor when determining surgical intervention. Attention should be paid to the presence of increased gas accumulation on rectal or radiographic examination.